All‐day wearable health monitoring system. Issue 4 (9th March 2022) - Han, Sang A; Naqi, Muhammad; Kim, Sunkook; Kim, Jung Ho
Abstract: Wearable devices are widely used in the smart healthcare monitoring system to detect changes in user parameters through applications such as wristwatches, bands, and clothing electronic skin. In addition, multimode devices enable monitoring of vital signs, helping diagnose and prevent diseases. A wearable device detects the user's biological signals such as body temperature, movement, heartbeat, and humidity level, transmits the information to the mobile phone, and sends the information to an emergency center/family/clinician through cloud computing or wireless communication systems. This all‐day monitoring system enables the user's status information to be monitored 24 h a day to ensure appropriate treatment, thereby facilitating highly personalized care due to its human‐centricity. When integrated with higher‐level infrastructure, it is expected to be useful in healthcare scenarios, providing benefits to multiple stakeholders. In addition, it will help protect people exposed to potentially life‐threatening environments such as military personnel, first responders, and deep‐sea and space explorers. In this review, the components for implementing an all‐day monitoring system are described, including the electrode design strategy for realizing a skin attachable e‐skin device. Issues related to flexible storage devices and recent research results are also discussed. Abstract : The use of an all‐day monitoring system in which a wearable device mounted to or implanted into the human body detects the user's bio‐signals and transmits that information through a communication system will facilitate highly personalized treatment owing to the system's user‐centricity. It is expected to excel in healthcare scenarios integrated with higher‐level infrastructure, benefitting multiple stakeholders.